2018
DOI: 10.1155/2018/7173920
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Benefits and Mechanisms of Action of the Bioactive Vegetal Alkaloid Berberine on Lipid Metabolism and Homeostasis

Abstract: Elevation of circulating levels of blood cholesterol, especially LDL cholesterol, and/or the decrease of HDL cholesterol levels have long been recognized as primary risk factors for developing atherosclerosis that leads to cardiovascular and cerebrovascular disease. Hypertriglyceridemia is an independent risk factor that is known to contribute to the development of atherosclerosis. Thus, various interventional efforts aimed at reducing hypercholesterolemia and hypertriglyceridemia have been practiced clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 136 publications
1
34
0
10
Order By: Relevance
“…Notably, numerous studies have demonstrated that BBR can reduce lipogenesis by down-regulating pparγ expression in different tissues (11,29,45,61,62) . Hence, the lipid-lowering effect of BBR was mainly attributed to the fact that it can mitigate lipid accumulation in liver through down-regulating lipogenesis and up-regulating lipolysis pathways, similar to mechanisms reported in mammals (14,42,61) .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Notably, numerous studies have demonstrated that BBR can reduce lipogenesis by down-regulating pparγ expression in different tissues (11,29,45,61,62) . Hence, the lipid-lowering effect of BBR was mainly attributed to the fact that it can mitigate lipid accumulation in liver through down-regulating lipogenesis and up-regulating lipolysis pathways, similar to mechanisms reported in mammals (14,42,61) .…”
Section: Discussionsupporting
confidence: 59%
“…Several studies reported that some feed additives could reduce liver lipid deposition and alleviate the adverse effects caused by HL diets, such as bile acids (8,9) , L-carnitine (10) , fenofibrate (11) , choline, betaine (12) and xylooligosaccharides (13) . Berberine (BBR) (18,5,6-dyhydro-9,10-dimethoxybenzo(g)-1,3benzodioxolo(5,6-a) quinolizinium) is an isoquinoline alkaloid isolated from Coptis chinensis (Chinese goldthread), Hydrastis canadensis (goldenseal), Berberis vulgaris (barberry) and other herbs (14) or manufactured by chemical synthesis. It has been commonly used in Chinese medicine for its antiinflammatory, antibacterial, antioxidant and antiapoptotic Abbreviations: accα, acetyl-CoA carboxylase α; ALT, alanine aminotransferase; AST, aspartate aminotransferase; BBR, berberine; Con, control; ConB, control diet with berberine supplementation; cpt1a, carnitine palmitoyltransferase 1a; fas, fatty acid synthase; FI, feed intake; g6pd, glucose 6-phosphate dehydrogenase; HL, high lipid; HLB, high-lipid diet with berberine supplementation; hsl, hormone-sensitive lipase; lpl, lipoprotein lipase; LPS, lipase; srebp-1, sterol regulatory element binding protein-1; VSI, viscerosomatic index; 6pgd, 6-phosphogluconate dehydrogenase.…”
mentioning
confidence: 99%
“…It is present in several medicinal plants, such as Berberis vulgaris, Coptis chinensis, Hydrastis canadensis, Coptidis rhizoma, Xanthoriza simplicissima, Phellodendron amurense, and Chelidonium majus. Berberine exhibits unusual biochemical and pharmacological activities, including antidiabetic [1], hypolipidemic [2], antihypertensive [3], anti-inflammatory [4], antidiarrheal [5], hepatoprotective [6], antidepressant [7], anticancer [8], antibacterial [9], and antiviral [10] properties. BBR is capable of penetrating all cell lines, but the cumulative concentration is the highest in Hep G-2 cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in the high-cholesterol animal model, the administration of HHT for 8 weeks significantly prevented the progression of thoracic aortic plaque with an anti-oxidative effect [ 13 ]. In particular, Berberine , a component of HHT, has been reported to reduce TC and LDL-C levels and increase high-density lipoprotein cholesterol (HDL-C) levels in animals and humans through mechanisms such as absorption of cholesterol in the intestine, removal of LDL receptor-mediated LDL-C, and conversion of cholesterol into bile [ 14 ]. In a randomized controlled trial (RCT) comparing HHT and statins in patients with hyperlipidemia, both groups exhibited significantly decreased TC, TG, and LDL-C and significantly increased HDL-C after treatment, compared to the levels before treatment.…”
Section: Introductionmentioning
confidence: 99%